2011
DOI: 10.1163/138577211x557549
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Functionality of the Organifier on the Physical Properties of Polyurethane Rigid Foam/Organified Nanosilica

Abstract: 3-Aminopropyltriethoxysilane (APTS) was used as coupling agent on the nanosilica surface and its effects on the physical properties of polyurethane rigid foam were compared with nanosilica modified with n-(2-aminoethyl)-3-aminopropyltrimethoxysilane (AEAP). Characterization and investigation of properties were done by Fourier transform infrared spectroscopy, thermogravimetric analysis, scanning electron microscopy, dynamic mechanical analysis and thermomechanical analysis. Also, the tensile properties were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…In comparison with other previous reports, the same tendency was also observed for the influence of different amounts of nano‐silica on the morphology of PUF 34,37 . According to Engin Burgaz, 35 the good dispersion of nanoparticles can help to increase the number of nucleation sites per unit volume in the PUF matrix leading to the formation of cells with smaller sizes and elevation of cell density.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…In comparison with other previous reports, the same tendency was also observed for the influence of different amounts of nano‐silica on the morphology of PUF 34,37 . According to Engin Burgaz, 35 the good dispersion of nanoparticles can help to increase the number of nucleation sites per unit volume in the PUF matrix leading to the formation of cells with smaller sizes and elevation of cell density.…”
Section: Resultssupporting
confidence: 81%
“…Meanwhile, the cellular morphology have not been improved in the case of 0.2, and 0.25 %Wt nano‐silica. This result is explained that the appropriate nano‐silica particles act as extra nucleation sites during foaming process which can lead to diminish the average cell size and also to obtain a more uniform distribution of cell size 34,35 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers showed that the use of a small amount of modified nanoclays and production of polyurethane-clay nanocomposite causes enhancement in mechanical and thermal properties, gas barriers and some other properties of such polymers remarkably [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] . The preparation of polyurethane-clay nanocomposites via in situ polymerization method has been the issue of many researches in past years [25,26,30,[40][41][42][43] .…”
Section: Introductionmentioning
confidence: 99%